Effectiveness of bat boxes for bat conservation and insect suppression in a Western Australian urban riverine reserve. (2nd December 2020) - Burgar, Joanna M.; Hitchen, Yvette; Prince, Jim
Abstract: Urban wetlands are important habitat for wildlife, particularly insectivorous bats which provide a key ecosystem service in suppressing insects. While claims are often made that bats consume high numbers of mosquitoes in a given night, the evidence for this claim is scant at best. The Canning River Regional Park (CRRP), an urban riverine reserve in Western Australia, has fauna conservation as a primary goal and mosquito control as a top priority. We took advantage of occupied bat boxes within the CRRP to determine the roosting bat species and their diet using non‐invasive DNA metabarcoding of bat faecal samples. The widespread and urban‐adapted Chalinolobus gouldii was the only bat species detected roosting in the bat boxes. This opportunistic forager consumed over 700 unique prey (operational taxonomic units; OTUs); only 14% of OTUs were assigned to either species or genus, representing seven insect orders. Mosquitoes were detected in 11% of the 90 faecal samples, over multiple years and in both the maternity and non‐maternity seasons. Assigned prey was predominantly Lepidoptera with 40% of the 49 Lepidoptera species negatively impacting humans. Urban riverine reserves are critical habitat for bats, which in turn, are crucial in providing the ecosystem service of insect suppression. Abstract : Urban wetlands are important habitat for wildlife, particularly insectivorous bats which provide a key ecosystem service in suppressing insects. We took advantage of occupied bat boxes within an urban riverine reserve to determine the roosting bat species and their diet using non‐invasive DNA metabarcoding of bat faecal samples. We detected only one bat species ( Chalinolobus gouldii ) roosting in the bat boxes, foraging on >700 unique prey, representing seven insect orders.